The Problem Of The Authority To Determine The Financial Losses Of The State On State Owned Enterprises (BUMN) - Hakim, Lukmanul; Farida Kaplele (Faculty of Law, Universitas Pekalongan, 2024)
This paper discusses the problems in determiningwhich institutions have the authority to determine thefinancial losses of the state to state-owned enterprises.Even though in existing legislation such as Law No. 15of 2006 on the Supreme Audit Agency which regulatesthe authority of the Supreme Audit Agency (BPK) andthe decision of the Constitutional Court (MK) No. 25of 2016 basically states that related to the calculation ofstate financial losses carried out by the BPK or otherinstitutions as long as declared by the BPK, but inpractice it is still found the fact that law enforcers suchas investigators and public prosecutors ignore thisprovision for various reasons. Therefore, this paperaims to reaffirm the authority of institutions that havethe authority to determine state financial losses to stateowned enterprises based on existing legislation. Thisstudy uses the type of normative legal research. Theproblem approach used in this study includes statuteapproach, conceptual approach and case approach.